SEC framework and no-action letter provide guidance on analyzing whether a digital asset is a security. Issue 4 (27th November 2019) - Berman, Kenneth J.; Hayes, Morgan J.; Kaplan, Matthew E.; Lim, Byungkwon; Murphy, Gary E.; Do, Yean; Steinberg, Jonathan R.
Abstract : Purpose: To analyze and draw conclusions from the "Framework for 'Investment Contract' Analysis of Digital Assets" (the "Framework"), released by the US Securities and Exchange Commission (the "SEC") on April 3, 2019, and the SEC's corresponding no-action letter to TurnKey Jet, Inc. ("TKJ"), which is the SEC's first no-action letter publicly agreeing with the view that the digital asset described therein is not a security. Design/Methodology/Approach: Explains how the Framework assists market participants in analyzing whether a digital asset is a security, by applying the Howey factors for identifying an investment contract. Discusses the SEC's TKJ Letter, highlighting the factors the SEC emphasized in its analysis of the Framework. Findings: While largely reiterating prior guidance, the Framework provides a helpful overview of the SEC's views on when a digital asset is a security and how to properly analyze the prongs of Howey with respect to digital assets. The Framework also leaves certain important questions unanswered, including, for example, whether digital assets distributed by means of a so-called "Airdrop" are securities under the Framework, and the extent to which the Framework is meant to interact with digital assets that were issued or otherwise operate on platforms that are primarily overseas. Originality/Value: Expert guidance from lawyers with broad experience in financial services, securities, investment funds, derivatives, and digital assets regulation and compliance.